2015
DOI: 10.1111/jnc.13167
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the high‐affinity choline transporter by wild‐type and Swedish mutant amyloid precursor protein

Abstract: The high-affinity choline transporter (CHT) is responsible for choline uptake into cholinergic neurons, with this being the rate-limiting step for acetylcholine production. Altering CHT protein disposition directly impacts choline uptake activity and cholinergic neurotransmission. Amyloid precursor protein (APP) interacts with CHT proteins and increases their endocytosis from the cell surface. The goal of this study was to examine regulation of CHT trafficking and activity by wild-type APP (APP wt ) and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…The purpose of the present study was to investigate the effect of Aβ peptides released into conditioned medium (CM) from neural cells expressing Swedish mutant APP (CM-APP Swe ) on CHT trafficking and activity, and to determine whether this is altered by anti-Aβ antibodies. We found recently that expression of APP Swe in neural cells decreases CHT function when compared to wild-type APP with this related to increased APP Swe processing (Cuddy et al, 2015 ). We now make the novel observation that treatment of neural cells with CM that contains Aβ peptides from cells expressing APP Swe decreases CHT co-localization with the early endosome marker EEA1 and lysosome marker LAMP-1, suggesting that Aβ-mediated inhibition of CHT function is related to a loss of CHT proteins from endocytic recycling compartments.…”
Section: Introductionmentioning
confidence: 94%
“…The purpose of the present study was to investigate the effect of Aβ peptides released into conditioned medium (CM) from neural cells expressing Swedish mutant APP (CM-APP Swe ) on CHT trafficking and activity, and to determine whether this is altered by anti-Aβ antibodies. We found recently that expression of APP Swe in neural cells decreases CHT function when compared to wild-type APP with this related to increased APP Swe processing (Cuddy et al, 2015 ). We now make the novel observation that treatment of neural cells with CM that contains Aβ peptides from cells expressing APP Swe decreases CHT co-localization with the early endosome marker EEA1 and lysosome marker LAMP-1, suggesting that Aβ-mediated inhibition of CHT function is related to a loss of CHT proteins from endocytic recycling compartments.…”
Section: Introductionmentioning
confidence: 94%
“…) and even more complexity is revealed by new findings that APP interacts with choline transport and its trafficking is sensitive to APP genetic mutants (Cuddy et al . ).…”
Section: Cholinergic Transmission Signalling and Pathobiologymentioning
confidence: 97%
“…Other possible targets here include a4-nicotinic AChRs which play a role in remodelling of spine architecture underpinning the cholinergic tuning of brain function and in associated hippocampal synaptic development and plasticity (Nordman et al 2014;Oda et al 2014). Even more surprisingly choline proves to be a potent direct regulator via both muscarinic and nicotinic AChRs of patterned activity within hippocampal networks (Fischer et al 2014) and even more complexity is revealed by new findings that APP interacts with choline transport and its trafficking is sensitive to APP genetic mutants (Cuddy et al 2015).…”
Section: Cholinergic Transmission Signalling and Pathobiologymentioning
confidence: 99%
“…CHT1 is specifically localized on presynaptic cholinergic nerve terminals and is directly involved in the high-affinity choline uptake (HACU) transport, a key regulatory step in the synthesis of ACh. CHT1 transporters actively transport choline from the synapsis back to the presynaptic terminals, where it is used for the de novo synthesis of ACh [18,19,20,21,22,23,24]. In contrast to AChE, however, the 3D structure of the transmembrane CHT1 is not known in details yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that CHT1 is localized predominantly within lipid rafts in neuronal membranes, where it colocalizes with the amyloid precursor protein (APP). It appears that APP regulates the cell surface levels of CHT1 via increased endocytosis and thus directly attenuates HACU activity [23,24]. The disruption of lipid rafts, e.g., by removing membrane cholesterol by methyl-β-cyclodextrine, thus enables in vitro investigations of CHT1 interactions under pathological conditions.…”
Section: Introductionmentioning
confidence: 99%